The effect of facility characteristics on patient safety, patient experience, and service availability for procedures in non-hospital-affiliated outpatient settings: A systematic review. - Nancy F Berglas; Molly F Battistelli; Wanda K Nicholson; Mindy Sobota; Richard D Urman; Sarah C M Roberts (PLoS ONE)
Background Over recent decades, numerous medical procedures have migrated out of hospitals and into freestanding ambulatory surgery centers (ASCs) and physician offices, with possible implications for patient outcomes. In response, states have passed regulations for office-based surgeries, private organizations have established standards for facility accreditation, and professional associations have developed clinical guidelines. While abortions have been performed in office setting for decades, states have also enacted laws requiring that facilities that perform abortions meet specific requirements. The extent to which facility requirements have an impact on patient outcomes-for any procedure-is unclear. Methods and findings We conducted a systematic review to examine the effect of outpatient facility type (ASC vs. office) and specific facility characteristics (e.g., facility accreditation, emergency response protocols, clinician qualifications, physical plant characteristics, other policies) on patient safety, patient experience and service availability in non-hospital-affiliated outpatient settings. To identify relevant research, we searched databases of the published academic literature (PubMed, EMBASE, Web of Science) and websites of governmental and non-governmental organizations. Two investigators reviewed 3049 abstracts and full-text articles against inclusion/exclusion criteria and assessed the quality of 22 identified articles. Most studies were hampered by methodological challenges, with 12 of 22 not meeting minimum quality criteria. Of 10 studies included in the review, most (6) examined the effect of facility type on patient safety. Existing research appears to indicate no difference in patient safety for outpatient procedures performed in ASCs vs. physician offices. Research about specific facility characteristics is insufficient to draw conclusions. Conclusions More and higher quality research is needed to determine if there is a public health problem to be addressed through facility regulation and, if so, which facility characteristics may result in consistent improvements to patient safety while not adversely affecting patient experience or service availability.